Religious Ideology Plurality of IAIN Kendari Students - M, Zulkifli; Insawan, Husain (Advances in Social Sciences Research Journal, 2022)
This study aims to describe the plurality of religious ideologies of IAIN Kendari students. The method used is descriptive qualitative with data analysis techniques, interviews and documentation, while data analysis is data collection, reduction, discussion, and conclusion. The results showed that: The plurality of religious ideology of IAIN Kendari students was (a) Persyarikatan Muhammadiyah as a movement to purify Islamic teachings through da’wah makruf nahi munkar preaching, building society in various aspects, both in the fields of aqeedah, worship, social, education, health and technology ; (b) Nahdhatul Ulama is engaged in the fields of religion, education, social, economy, adhering to the Ahlussunnah waljama’ah concept, sourced from al-Qur’an, sunnah, which is a Shafi’i school; (c) Tabligh Jamaah is a global education and missionary movement with the principle of kalimah tauhid, upholding salât, knowledge and dhikr, glorifying every Muslim, sincere, improving intentions, preaching to Allah and khuruj in His way with tabligh; (d) The Muslim Brotherhood has a Sunni ideology, Islamic democracy, and religious conservatism, realizing the formation of individual Muslim, household, nation and Islamic government figures; (e) Indonesian Islamic Da’wah Institution is based on the spirit of carrying out the teachings of Islam based on Al- Qur’an and Al-Hadith, through the implementation of mahdhah and ghairu mahdhah worship as the implementation of human position towards Al-Khaliq by worshiping solely to Him; (f) The Salafi movement returns to the teachings of Islam as exemplified by the Prophet seeing his friends, tabi’in and tabi’ut tabi’in; (2) Plurality map of religious ideology in IAIN Kendari students in various understandings, Muhammadiyah, Nahdhatul Ulama, Tablighi Jamaah, Muslim Brotherhood, Indonesian Islamic Da’wah Institution, and Salafi; (3) The factors that influence are internal factors, the influence of fellow students on Islamic studies, the socio- cultural background of students’ economics.